2015
DOI: 10.3389/fmicb.2015.00940
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear electrical impedance spectroscopy of viruses using very high electric fields created by nanogap electrodes

Abstract: Our living sphere is constantly exposed to a wide range of pathogenic viruses, which can be either known, or of novel origin. Currently, there is no methodology for continuously monitoring the environment for viruses in general, much less a methodology that allows the rapid and sensitive identification of a wide variety of viruses responsible for communicable diseases. Traditional approaches, based on PCR and immunodetection systems, only detect known or specifically targeted viruses. We here describe a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The information about completely label-free EIS virus detectors is presented in Refs. [118,119]. To summarize, the EIS-based virus sensing technologies provide a hopeful tool for fighting with various virus diseases like immunodeficiency syndrome, dengue virus-infection, and, highly likely, COVID19.…”
Section: Bio-matter and Biosensoricsmentioning
confidence: 99%
“…The information about completely label-free EIS virus detectors is presented in Refs. [118,119]. To summarize, the EIS-based virus sensing technologies provide a hopeful tool for fighting with various virus diseases like immunodeficiency syndrome, dengue virus-infection, and, highly likely, COVID19.…”
Section: Bio-matter and Biosensoricsmentioning
confidence: 99%
“…Marcali and Elbuken exploited an impedimetric detection of agglutinated red blood cells in microdroplets with a droplet-based microfludic system. Yamamoto and co-workers reported on a simple device for the detection of viruses between nanogap electrodes using nonlinear EIS. Depending on the differences in the impedance of virus types and virus concentration in the virus solution, the approach could distinguish and detect their approximate concentrations.…”
Section: Immunosensors Based On Impedancementioning
confidence: 99%
“…It is well reported that the low-frequency dielectric response is dominated by the ionic relaxation of the buffer [32,41,42,43], complicating detection. The complex composition of the PBS buffer (0.01 M phosphate buffer, 2.7 mM KCl, 0.137 M NaCl) may be the source of this behaviour.…”
Section: Dielectric Spectroscopy Sensing Of Dnamentioning
confidence: 99%